Endodontic Management of a C-shaped Mandibular Second Premolar with Four Canals and Four Apical Foramina: A Case Report - Jafari, Zahra; Kazemi, Ali; Rahmatian, Mohammadreza (Iranian Endodontic Journal, 2025)
A thorough understanding of root canal morphology is critical for achieving predictable outcomes in endodontic therapy. Anatomical variations in mandibular second premolars are uncommon compared to other teeth, and the coexistence of a C-shaped root canal configuration with four independent canals and four separate apical foramina is exceptionally rare. This case report describes the nonsurgical endodontic management of a mandibular second premolar exhibiting this unique morphology, confirmed through cone-beam computed tomography (CBCT) and magnification. A 52-year-old male was referred by a prosthodontist for elective root canal treatment before post placement. CBCT imaging revealed a C-shaped root in the coronal third that bifurcated into four separate canals at the midroot level, each terminating in an independent apical foramen. Nonsurgical treatment was performed over two visits, using meticulous chemo-mechanical preparation, intracanal calcium hydroxide dressing, and warm vertical compaction obturation. At the 9-month follow-up, the tooth was functional, asymptomatic, and radiographically stable. This case underscores the importance of preoperative assessment with advanced imaging and magnification in identifying and successfully treating rare endodontic anatomies.